Voix d’enfants canadiens et racisme catholique : L’ŒUVRE de la Sainte-Enfance au XXe siècle - Gaudreault, Benoit; Larochelle, Catherine (Histoire sociale / Social History, 2023)
L’Œuvre de la Sainte-Enfance connut un succès gigantesque auprès des enfants catholiques canadiens entre les années 1920 et 1960. À travers cette implication missionnaire, les enfants ont été formés à croire en leur capacité de rédemption de l’enfance éloignée. La Sainte-Enfance transformait les enfants lointains en possession, commodités, jeux et personnification à la disposition de l’imagination géographique et émotive des jeunes Canadiens français et Canadiennes françaises. Elle le faisait en s’appuyant sur des techniques pédagogiques et des pratiques antérieures et transnationales de performances racialisées. Comment peut-on donc faire l’histoire de la participation des enfants canadiens-français à cette œuvre en analysant leur propre voix ? Par l’étude d’un corpus de 803 lettres envoyées par des enfants, nous disséquons comment l’Œuvre de la Sainte-Enfance rythmait le quotidien des jeunes Canadiens français et Canadiennes françaises et quel univers de représentations raciales et genrées elle leur offrait.
Number: 115

Les représentations des Premiers Peuples et le colonialisme d’occupation dans les manuels scolaires d’histoire (1920-1960) - Gaudreault, Benoit (Université de Montréal, 2022)
My master’s thesis examines the representations of First Peoples in French-language history textbooks produced and used in Quebec between 1920 and 1960, with a particular focus on those intended for elementary school children. This research is at the crossroads of studies on Quebec colonialism, childhood history and the study of representations. Several theories emanating from visual studies, othering and performance studies are also mobilized in my study of history textbooks. By positioning itself at the intersection of this mosaic of historiographies and conceptual approaches, my master’s thesis answers the following questions: how are the First Peoples in Canada represented in French-language history textbooks produced between the 1920s and the 1960s and to what extent are these representations at odds with the previous period? How are these representations mobilized in the Quebec colonial imagination? How is the colonial image of the ‘imaginary Indian’ received, appropriated and performed by children? My study contributes to a historiography exploring history of representations of the First Peoples in history textbooks since the beginning of public education in Quebec. The first chapter explores three historiographical fields on which my dissertation draws: children's history, settler colonialism, and representations of First Peoples in North American popular culture. Chapters two and three are devoted, in order, to the analysis of history textbooks produced between 1920 and 1950 and those between 1950 and 1960. I show that the figure of the Indian is mobilized by the authors of the first period’s textbooks to justify the dispossession and colonial violence of the past, notably through the use of political, moral and genealogical arguments. In the latter period’s, more nationalistic series of textbooks, the authors reiterate these same ideas, but with a stronger emphasis on the idea of the ‘civilizing mission’ to the point of cleansing the Quebec historical narrative of its original violence. Furthermore, I argue that these textbooks show the continuation of colonialism in the present. First Peoples no longer disappear from the narrative after the Conquest, as was the case in history textbooks before 1950, but they are still subject to a colonial discourse that denigrates and invisibilizes them, while attempting to justify the dispossession of their lands.
Keywords: Altérité; Autochtones; Canadian history / Histoire du Canada (UMI : 0334); Childhood; Colonialisme d'occupation; First Peoples; History; Manuel scolaire; Otherness; Premiers Peuples; Représentations; Settler colonialism; Textbook; Visual studies; Éducation

Enfants, enfance(s) et agentivité : un champ historique en transformation - Cardinal-Lamarche, Renaud; Gaudreault, Benoit; Larochelle, Catherine; Lavergne, Rafael; Thibault, Laura-Marie (Historical Studies in Education / Revue d'histoire de l'éducation, 2021)
This article addresses one of the central questions that has animated the field of children's history in recent years: how to go beyond the paradigm of agentivity in the interpretation of the evidences left by children? What interpretative schemes are proposed to replace it? Before addressing this issue and the archival and methodological challenges inherent to it, we propose an overview of the field of children's history. The goal is to offer a French-speaking readership an overview of some of the epistemological reflections that animate this branch of the historical discipline. Exploring themes such as the relationship between voice, experience, emotion and agentivity, the process of constructing the narrative of childhood through archives, and the benefits of transnational perspectives, this text is a plea for a renewal of children's history in the francophone world.
Keywords: History of childhood; History of children; agency; childhoods; children; voices